Refleksi atas Pandemi Covid-19 Berdasarkan Perspektif Teori Psikoanalisis Humanis Erich Fromm - Theguh Saumantri; Anwar Sanusi (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2022)
The world is currently shocked by a new virus, namely severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) or what is known as covid-19. The virus, which was first discovered in Wuhan, China, has claimed thousands of human victims, including in Indonesia. Many things have happened in terms of humanity in this Covid-19 phenomenon. The occurrence of social distancing, solidarity to help each other even excessive concern for the victims of covid-19. Which in the end has an impact on the exclusion and rejection of these covid-19 victims, which should not have happened. According to a German philosopher, Erich Fromm. In his humanist psychoanalytic theory, Erich Fromm, basically humans under any circumstances have social attachments in the form of love and cooperation with others.